تأثير لعبة الأسرار المتسلسة في ترقية مهارة الاستماع لدى طلاب الصف الثامن بالمدرسة المتوسطة الإسلامية الحكومية 4 مندايلينج ناتل - Apsah; Isra Hayati Darman; Fadlan Masykura Setiadi (PT. Willy Print Art, 2025)
Researchers chose this title because of problems in learning listening skills, such as: student scores in learning Arabic language learning is lower than the average set by the school which is 7,30 teacher-centered learning that makes students play alone, lack of interest in learning students in learning, innappropriate selection of methods and media. This study aims to analyze the effect of whispering chains on listening proficiency, analyzing students’ tendency to use the whispering chain game on listening proficiency and reveal the supporting and inhibiting factors in listening proficiency. Listening proficiency and reveal the supporting and inhibiting factors in teaching whispering chain game. This research is quantitative research, using experimental method with posttest-only control design. Population in this study is a class VIII student at MTs Negeri 4 Mandailing Natal, totaling 133 students. And researchers took research samples in class VIII-C (experimental) consists of 32 students and class VIII-B (control) consisting of 32 students. Researchers used data collection methods, namely test, questionnaire, observation and interview. After the researcher gave the test to the students, this study obtained average test score in class VIII– C experimental score of 77,18 and 54,37 in class VIII-B control with the result of hypothesis test of language game on listening skill of Students was 3,81 with sufficient category. After calculation Table value was obtained at 5% level which is 2,03 and shows that the null hypothesis ( ) is rejected and the alternative hypothesis ( ) is accepted. The tendency of student to complete because the average result of the student tendency 85,79. Support factors in the use of chain whispering game are student, textbooks, and class room, and inhibiting factors are environmental factors, time, and so on.